Advanced soil mechanics - Das, Braja M. (CRC Press, Taylor & Francis Group, 2014)
"An upper level undergraduate and begging graduate-level textbook, this new edition of a bestseller includes new sections on the AASHRO Soil Classification System and Soil Compaction as well as along with several recently developed empirical relationships for estimation of maximum dry unit weight based on compaction energy. It covers the procedures to estimate stress and displacement based on the theory of elasticity for place strain and three-dimensional cases and solutions for the determination of vertical stress due to various loading conditions on Westergaard-type material have been added. Several new example problems have been added to every chapter"--